2014
DOI: 10.1038/nm.3440
|View full text |Cite
|
Sign up to set email alerts
|

The ryanodine receptor store-sensing gate controls Ca2+ waves and Ca2+-triggered arrhythmias

Abstract: Spontaneous Ca2+ release from intracellular stores is important for various physiological and pathological processes. In cardiac muscle cells, spontaneous store overload-induced Ca2+ release (SOICR) can result in Ca2+ waves, a major cause of ventricular tachyarrhythmias (VTs) and sudden death. The molecular mechanism underlying SOICR has been a mystery for decades. Here, we show that a point mutation E4872A in the helix bundle crossing (the proposed gate) of the cardiac ryanodine receptor (RyR2) completely abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
245
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(260 citation statements)
references
References 78 publications
11
245
0
4
Order By: Relevance
“…Specifically, the gain-of-function (GOF) RYR2 mutants (Q4201R and V4653F) yield increased ER Ca 2ϩ leakage, whereas the loss-of-function (LOF) RYR2 mutant (A4860G) exhibits reduced Ca 2ϩ leak into the cytosol as compared with WT RYR2 (6,42). Consistent with the effect of TG and A23, GOF RYR2 mutants induced PCSK9 expression (Fig.…”
Section: Ermentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the gain-of-function (GOF) RYR2 mutants (Q4201R and V4653F) yield increased ER Ca 2ϩ leakage, whereas the loss-of-function (LOF) RYR2 mutant (A4860G) exhibits reduced Ca 2ϩ leak into the cytosol as compared with WT RYR2 (6,42). Consistent with the effect of TG and A23, GOF RYR2 mutants induced PCSK9 expression (Fig.…”
Section: Ermentioning
confidence: 99%
“…F, to determine the effect of ER stress-inducing conditions via non-pharmacologic means on PCSK9 expression, HuH7 cells were exposed to medium deficient in either Ca 2ϩ , glucose, amino acids, or sterol for 24 h. G, in addition, the role of ER Ca 2ϩ loss on PCSK9 expression was examined using HEK293 cells that stably overexpress tetracycline-inducible GOF or LOF RYR2 mutants using immunoblots. GOF RYR2 mutant cell lines (Q4201R and V4653F) exhibit increased ER Ca 2ϩ leakage, whereas LOF RYR2 mutant (A4860G) exhibits reduced ER Ca 2ϩ leak compared to WT cells (6,42). Differences between treatments were assessed with paired Student's t tests, and all values are represented as mean Ϯ S.D.…”
Section: Ermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the homogeneous model appears to capture most of the experimentally observed behaviors, and in addition provides a key framework for future exploration of the role of heterogeneity. The RyR model developed by Restrepo et al (14) incorporated calsequestrin-mediated SR luminal Ca regulation, whereas recent experiments have demonstrated a luminal Ca-sensing site in the RyR mediating this effect (63). Moreover, the refractoriness of Ca release is controversial, with a wide range of experimentally measured values (64)(65)(66)(67)(68)(69) and different proposed causes.…”
Section: Limitationsmentioning
confidence: 99%
“…RyRs have been proposed to sense the Ca 2+ concentration inside the SR via an allosteric signal involving calsequestrin, triadin and junctin [12]. Recently, it has been shown that the RyRs can also sense the Ca 2+ concentration inside the SR directly [13,14]. Alterations of the free SR Ca 2+ concentration ([Ca 2+ ] SR ) can be explained by a variety of dysfunctions of elements that participate in the SR Ca 2+ uptake/release balance (e.g.…”
Section: Introductionmentioning
confidence: 99%